2010
DOI: 10.5089/9781455201334.001
|View full text |Cite
|
Sign up to set email alerts
|

Procyclicality in Central Bank Reserve Management: Evidence From the Crisis

Abstract: This Working Paper should not be reported as representing the views of the IMF.The views expressed in this Working Paper are those of the author(s) and do not necessarily represent those of the IMF or IMF policy. Working Papers describe research in progress by the author(s) and are published to elicit comments and to further debate.A decade-long diversification of official reserves into riskier investments came to an abrupt end at the beginning of the global financial crisis, when many central bank reserve man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…Finally, the recent crisis has demonstrated that interventions can only be effective if central bank reserves are invested in saved assets. The crisis stopped and even reversed the trend towards riskier investments of reserves, being motivated by higher expected returns (Pihlman and van der Hoorn, 2010).…”
Section: Implications For Intervention Policy In Emerging Marketsmentioning
confidence: 99%
“…Finally, the recent crisis has demonstrated that interventions can only be effective if central bank reserves are invested in saved assets. The crisis stopped and even reversed the trend towards riskier investments of reserves, being motivated by higher expected returns (Pihlman and van der Hoorn, 2010).…”
Section: Implications For Intervention Policy In Emerging Marketsmentioning
confidence: 99%
“…South Korea's central bank became the latest official sector buyer, announcing the purchase 4 The gold price traded higher at US$1,714 per ounce in reaction to the news that Standard & Poor's downgraded the US credit rating to AAþ from AAA stripping the US of the top rating it held for 70 years (Traynor, 2011). 5 However, Pihlman and Hoorn (2010) contend that central banks begun to reveal slowly, but surely more and more information about their reserve management activities in their annual reports. 6 It is a statutory requirement that the gold producing mines sell gold to the central bank.…”
Section: Role Of Central Banks In the Gold Marketmentioning
confidence: 98%
“…As a result, foreign exchange reserves with the central banks, irrespective of fixed or flexible exchange rate regimes, are considered necessary. Pihlman and Hoorn (2010) places the objectives for reserves in the form of umbrella of "self-insurance" against financial shocks and sudden stops in the access to international capital markets. For EMEs, the self-insurance motive probably explains a good portion of the buildup in reserves since the late 1990s, especially for those countries that heavily suffered in the series of crises.…”
Section: Gold Reserves and Central Banksmentioning
confidence: 99%
“…As Pihlman and van der Hoorn (, p. 11) remark, “[the] most extensive and consistent dataset available on reserve levels and composition is collected by the IMF. This dataset consists of reserve data from countries that voluntarily subscribe to the Special Data Dissemination Standard (SDDS) and report the data according to a common template.” Two features of the IMF's SDDS dataset make it informative for this study .…”
Section: Public Information On Central Bank Activities In Derivativesmentioning
confidence: 99%